Learning Outcomes and Public Trust in Higher Education - Loukkola, Tia; Peterbauer, Helene (International Higher Education, 2020)
Learning outcomes are increasingly used in qualifications frameworks and quality assurance processes. As such, they aim to secure and foster public trust among education providers. Yet, against the backdrop of internationalized higher education, questions arise on whether learning outcomes can fulfill this function on a global scale and whether there is a way, and need, to verify if learning outcomes have been achieved.